STUDENTS’ INTEREST IN PURSUING EDUCATION: EVIDENCE FROM THE PERSPECTIVE OF LEARNING MOTIVATION AND PARENTS’ SOCIO-ECONOMIC STATUS - Mohamad Muspawi; Lusi Anesa (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This research aimed to find out the effect of learning motivation and parents' socio-economic status on the students’ interest to continue study in master degree at Education Administration Study Program in Jambi University. This research used quantitative approach with survey research design. The population was the students of Education Administration Study Program batch 2015 and 2016 in Jambi University which consisted of 71 students. This study used the entire population as sample to obtain more accurate and reliable data. Closed questionnaire using Likert scale was the instrument of collecting data. The data analysis technique used was descriptive statistical analysis. The findings indicated that there was influence of learning motivation on the students’ interest to continue study in master degree, there was influence of parents' socioeconomic status on the students’ interest to continue study in master degree, and there was influence of learning motivation and parents' socioeconomic status toward the students’ interest to continue study in master degree.Abstrak:Penelitian ini bertujuan untuk mengetahui pengaruh motivasi belajar dan status sosial ekonomi orang tua terhadap minat belajar siswa untuk melanjutkan studi S2 di Program Studi Administrasi Pendidikan Universitas Jambi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain penelitian survei. Populasi penelitian ini adalah mahasiswa Program Studi Administrasi Pendidikan angkatan 2015 and 2016 di Universitas Jambi yang terdiri dari 71 mahasiswa. Penelitian ini menggunakan seluruh populasi sebagai sampel untuk mendapatkan data yang lebih akurat dan dapat diandalkan. Kuesioner tertutup menggunakan skala Likert adalah instrumen pengumpulan data. Teknik analisis data yang digunakan adalah analisis statistik deskriptif. Temuan menunjukkan bahwa ada pengaruh motivasi belajar terhadap minat siswa untuk melanjutkan studi di tingkat magister, ada pengaruh status sosial ekonomi orang tua terhadap minat siswa untuk melanjutkan studi di tingkat magister, dan ada pengaruh motivasi belajar dan status sosial ekonomi orang tua terhadap minat siswa untuk melanjutkan studi di tingkat master.